Computational Fluid Dynamics Hydrodynamic Analysis of a Cross‐Orthogonal Fixed‐Valve Tray. Issue 3 (30th January 2014) - Sun, Jinsheng; Luo, Xubo; Jiang, Shuo; Wang, Wenping; Lyu, Hao; Wang, Pei; Gao, Hong
Abstract A computational fluid dynamics model was developed to investigate the hydrodynamic characteristics of a novel orthogonal fixed‐valve tray, which offers a larger effective contact perimeter under the same orifice area than its previously reported counterparts. The liquid‐gas phases were simulated in the Eulerian framework, with the interphase momentum transfer source term based on the experimentally obtained liquid hold‐up correlation. The simulation results were consistent with the experimental data. In addition, the gas hold‐up profile of this new design was compared with its triangular cousin under the conditions of a typical run, showing that the former has a higher froth height, which indicated better interphase contact on the tray.